Failure Analysis on Titen Proto-XX Car Chasis - Jatisukamto, Gaguk; Qoryah, Rika Dwi Hidayatul; Mulyadi, Santoso (Journal of Mechanical Engineering Science and Technology (JMEST), 2019)
The car chassis as a skeleton supports all loads and is the most important component. Car chassis requirements must be rigid, twisting resistant, vibration resistant and resistant to fatigue. This study aims to find the cause of the failure of the Titen Proto-XX car chassis connection. The research methodology was conducted by testing the composition of materials and structural analysis using Ansys Workbench Release 15.0 software. The conclusion of the research is that the skeletal structure material uses Aluminum AA series 1XXX with Al content greater than 99.5%, the welding ability is low, causing a failure in the welded joint. The rivet connection failure is caused by the stress concentration in the rivet holes in the plates so that the connection crack propagation occurs.